Kinetic study on phosphate removal from aqueous solution by biochar derived from peanut shell as renewable adsorptive media - Jung, K. -W.; Hwang, M. -J.; Ahn, K. -H.; Ok, Y. -S. (SPRINGER, 2015)
As an alternative strategy for phosphate removal, biochar (black carbon) has characteristics superior to those of widely used adsorptive media, from both economic and environmental points of view. In this study, various types of biochar derived from oak wood, bamboo wood, maize residue, soybean stover, and peanut shell were tested for evaluation of phosphate removal. After 24 h of reaction time, the phosphate removal was limited (2.0-9.4 %) in case of general adsorptive media. However, interestingly, among various biochars, peanut shell-derived biochar (PSB) exhibited the best performance, showing the highest phosphate removal rate, 61.3 % (3.8 mg PO4-P g PSB-1). We attribute this high value to the proper structural properties of PSB, such as BET-specific surface area of 348.96 m(2) g(-1) and mineral/phosphorus ratio (Mg/P = 3.46 and Ca/P = 47.6). Adsorption equilibrium and kinetics of phosphate at different temperature (10, 20, and 30 A degrees C) were well explained in the whole experimental region by Langmuir isotherm and pseudo-second-order kinetic models, respectively. The maximum adsorption capacity of PSB was 6.79 mg g(-1) for phosphate at 30 A degrees C. These findings suggest that PSB has great potential as an alternative and renewable adsorptive media for phosphate removal.
Keywords: PHOSPHORUS REMOVAL; SOYBEAN STOVER; WATER; CARBON; SOIL; EQUILIBRIUM; BIOSORPTION; MODELS